Fostering an Appropriate Stage for Teaching Implementation in EFL Students’ Reading Comprehension by Developing Materials based on Oxford Word Level - Fazl Ahmad Habib; Windy Citra Negara; Linda Mayasari (PROCEEDING UMSURABAYA, 2026)
Reading skill relies heavily on the reader’s comprehension. In English as a Foreign Language (EFL) classrooms, the presence of more than one language creates variation in both context and content during the reading process. In Indonesia, EFL learners often rely on teachers who assist their reading comprehension by translating unfamiliar words. This occurs because many students are not yet familiar with the vocabulary used in texts. This study focuses on teacher-created materials designed to support students’ understanding. The teacher used the Oxford 3000 word list to determine difficulty levels. The study employed Classroom Action Research (CAR) as its methodology, consisting of two cycles: the first cycle applied the direct teaching method, while the second implemented problem-based learning. In both cycles, the teacher provided materials based on the Oxford word levels. The results indicated that students' reading comprehension and motivation improved. The study suggests that formative assessment should be further developed in future research.